Management of Student Moral Education in Islamic Boarding School - Nurjaman, Jajang; Zainuddin, Ammar; Rusydi, Ibnu; Warti'ah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study originates from an initiative undertaken by the Daarul Hijrah Walhidayah Islamic Boarding School in Mekarsari Pancatengah, Tasikmalaya. The institution has devised programs to mold the character of its students and foster values of discipline and positive conduct. These initiatives encompass communal prayers, Quranic studies, environmental stewardship, aiding sick peers, maintaining discipline within the boarding school, and other endeavors that promote constructive values. The research endeavors to explore two primary facets: (1) the management of the boarding school, encompassing the planning, execution, and assessment of programs, and (2) the cultivation of ethical behavior at the Daarul Hijrah Walhidayah Islamic Boarding School in Mekarsari Pancatengah, Tasikmalaya, achieved through activities like communal gatherings, religious instruction, recitations, memorials, cemetery visits, and commemorations of historical struggles. Research findings reveal a well-organized management structure at Daarul Hijrah Walhidayah, from initial program design to evaluation. The instilling of student ethics occurs through regular activities such as communal gatherings, religious instruction, recitations, memorials, cemetery visits, and commemorations of historical struggles, while ongoing assessments of character education are conducted consistently and efficiently.